Performance Indicators of Basic Infrastructure of Kotaku Program (The City without Slums) - Tribhuwana, Awliya; Farhan, Ohan (Semarang State University, 2020)
Abstract. Wotgali Village is a slum area. The aim of the current research is to find out the performance of slum base infrastructure using Lakip (Government Agency Accountability Report) of KOTAKU (City without Slums) Program. The first step was performed by identifying the initial settlement (base line), then some treatments on the facilities and infrastructure (finish line), performance evaluation stages of the preparation, planning, implementation, and sustainability stages. The research used qualitative and quantitative approach. Qualitative measurement began with a numerical assessment of the results on the level of regional slum. In addition, quantitative data used the Lakip simulation using results of the KOTAKU program stage performance. Results of the initial condition reach value of 32%. It is categorized as slight slums with an average sectoral slum of 36.68%. Basic infrastructure development which has final technical reached 24% and is included in slight slum with an average sectoral of 27.50%. The performance of LAKIP Kotaku was in preparation phase 90.46% (very good performance), planning stage was 89.93% (very good performance), implementation stage was 90.25% (very good performance), sustainability stage was 85.21% (better performance). Thus, the achievement of KOTAKU program is 85.19% with a range of value of 80-90. The value is included as better performance result. Results of the analysis can be concluded that level of slum can be reduced to 19% (not slum) by creating some improvements to basic facilities and infrastructure. In the following year, involving Lakip Performance, the planning stage can be enhanced through community participation and active involvement.